2015
DOI: 10.1007/s11136-015-1210-5
|View full text |Cite
|
Sign up to set email alerts
|

The EORTC QLQ-CR29 quality of life questionnaire for colorectal cancer: validation of the Dutch version

Abstract: PurposeTo validate the Dutch version of the EORTC QLQ-CR29 quality of life questionnaire for colorectal cancer.MethodsWe translated and pilot-tested the original questionnaire in the Netherlands, following EORTC guidelines. We assessed factor structure, reliability and construct validity in different samples of patients from four hospitals.ResultsOf 296 patients, 236 (80 %) returned the questionnaire, and 27 out of 48 patients returned the retest questionnaire. In addition to the original three scales, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 8 publications
9
62
2
Order By: Relevance
“…The findings of our study are congruent with the original validation study (Whistance et al, 2009), as well as the Spanish (Arraras et al, 2011), Dutch (Stiggelbout et al, 2016), and Korean (Ihn et al, 2015) validation studies. The findings of our study are congruent with the original validation study (Whistance et al, 2009), as well as the Spanish (Arraras et al, 2011), Dutch (Stiggelbout et al, 2016), and Korean (Ihn et al, 2015) validation studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of our study are congruent with the original validation study (Whistance et al, 2009), as well as the Spanish (Arraras et al, 2011), Dutch (Stiggelbout et al, 2016), and Korean (Ihn et al, 2015) validation studies. The findings of our study are congruent with the original validation study (Whistance et al, 2009), as well as the Spanish (Arraras et al, 2011), Dutch (Stiggelbout et al, 2016), and Korean (Ihn et al, 2015) validation studies.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we assessed the validity and reliability of the Polish translation of the EORTC QLQ-CR29 in a sample of Polish patients with CRC. The findings of our study are congruent with the original validation study (Whistance et al, 2009), as well as the Spanish (Arraras et al, 2011), Dutch (Stiggelbout et al, 2016), and Korean (Ihn et al, 2015) validation studies. Our analysis found that the Polish translation of the QLQ-CR29 had test-retest reliability, internal consistency, and multi-trait results similar to the original English version of the questionnaire.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Three of the 4 scales in the questionnaire showed better internal consistency than the original article (Whistance et al, 2009) and comparable results to other translated versions (Ihn et al, 2015;Magaji et al, 2015;Stiggelbout et al, 2016;Lin et al, 2017). However, the body image scale had a low internal consistency when all 3 questions were included.…”
Section: Discussionmentioning
confidence: 66%
“…At T0, T2 and T3, we administered the EORTC QLQ-CR29 [28] to assess fecal incontinence and sexual problems. We report the six-item incontinence subscale (a ¼ 0.63-0.78; range scores, 0-100) and the two single, gender-specific items assessing sexual interest (range scores, 1-4).…”
Section: Presence and Perceived Impact Of Treatment Harmsmentioning
confidence: 99%